Nickel oxide modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide as well as preparation method and application of nickel oxide modified carbon black catalyst
Through nickel oxygen reinforcement carbon black catalysts, the electrical catalytic restoration of the O2 generating H2O2 process of the intermediate combination is too strong, and the H2O2 generation of high selectivity and high efficiency has been realized, and it has extensive industrial application potential.
Patent Information
- Application Number
- CN202411559292.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
AI Technical Summary
In the process of electrocatalytic reduction of O2 to generate H2O2, the intermediate *OOH binds too strongly to the reaction site, causing the ORR process to turn to the 4-process, the product is converted to H2O, and the precious metal catalyst costs are high and the earth's abundance is low. Difficult to apply on a large scale.
Using nickel oxygen reinforcement charcoal black catalysts, by introducing oxygen-containing energy groups on the surface of carbon black, adsorbing NI-N4 mats, and using high-temperature carbonization treatment to anchor the NI single atom in the carbon black carbon grid, and then remove NI through acid erosion to remove NI Nano particles, obtained Ni single atom catalysts modified by oxygen -containing power group.
This catalyst maintains a high H2O2 selectivity (> 92%) in a large voltage window of 0.2-0.7 V (VS.RHE). The Faraday efficiency of H2O2 in the mobile electrolytic battery is close to 100%, which can run 24 H stably. The H2O2 yield is 6.73 mol · GCAT-1 · H-1, showing a broad application prospect.
Smart Images

Figure CN119372704A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic synthesis, and specifically relates to a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide and a preparation method thereof, and also relates to the application of the catalyst in the reaction of reducing O2 to generate H2O2. Background Art
[0002] As one of the 100 most important chemicals in the world, hydrogen peroxide (H2O2) is a valuable environmentally friendly oxidant with a wide range of applications, from providing clean water to synthesizing valuable chemicals and as a potential energy carrier. H2O2 is produced industrially using the anthraquinone process, which uses hydrogen as a production feedstock and is an energy-intensive method, thus limiting the potential of H2O2 as a sustainable and low-cost green oxidant.
[0003] In recent years, people have studied the synthesis of H2O2 from thermal catalysis of H2 and O2. However, this thermal catalytic route to generate H2O2 is also expensive, and more importantly, it is dangerous due to the potential risk of explosion in thermal catalysis. A safe and reliable alternative is to selectively generate H2O2 from oxygen through the oxygen reduction reaction (ORR). Certain precious metal catalysts, such as AuPt-Ni alloy, Pt / sulfur-doped zeolite template carbon and Au-Pd nanoalloy, have shown good performance in the electrocatalytic reduction of O2 to H2O2. However, the high cost and low earth abundance of these precious metals make it difficult for such catalysts to be used in large-scale practical applications.
[0004] In the process of electrocatalytic reduction of O2 to generate H2O2, the most critical intermediate is *OOH. *OOH binds too strongly to the reaction site, which will cause the ORR process to shift to 4 e - process, resulting in the final product being converted into H2O. Single-atom catalysts (SACs) have the advantages of adjustable electronic structure and maximum atomic utilization efficiency, showing good oxygen reduction catalytic activity, and are good catalysts for catalyzing O2 to H2O2. However, most of the previous researchers focused on transition metal single atoms such as Fe and Co. Single-atom catalysts such as Fe and Co have high ORR activity, but these two single-atom catalysts will make the ORR process more biased towards 4e - process, the selectivity for H2O2 is not high.
[0005] Based on this, providing a single-atom catalyst that can both ensure ORR activity and improve H2O2 selectivity is a technical problem that needs to be solved urgently. Summary of the invention
[0006] One of the objects of the present invention is to provide a method for preparing a nickel-oxygen modified carbon black catalyst having both ORR activity and H2O2 selectivity for electrocatalytic synthesis of H2O2.
[0007] A second object of the present invention is to provide a nickel-oxygen modified carbon black catalyst having both ORR activity and H2O2 selectivity for electrocatalytic synthesis of H2O2.
[0008] The third object of the present invention is to provide a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide and its application in the reaction of reducing O2 to generate H2O2.
[0009] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, comprising the following steps: S1. Introducing oxygen-containing functional groups on the surface of carbon black to obtain oxidized carbon black; S2, dissolving the nickel salt and the nitrogen-containing organic ligand in a solvent, and mixing them thoroughly to obtain a first product containing a Ni-N4 complex; adding the oxidized carbon black to the first product, heating the product so that the Ni-N4 complex is adsorbed on the surface of the carbon black, continuing to heat the product to remove the solvent, and then grinding the product to obtain a powdery second product; S3, subjecting the second product to high-temperature carbonization treatment under a protective atmosphere to obtain a third product in which Ni single atoms and Ni nanoparticles coexist; S4. Removing the Ni nanoparticles in the third product by acid etching to obtain a final product.
[0010] The general idea of the present invention is as follows: The present invention first introduces oxygen-containing functional groups on the surface of carbon black, then uses this as a substrate, first adsorbs Ni-N4 complexes on the surface of carbon black, and then uses high-temperature carbonization treatment to anchor Ni single atoms in the carbon grid of carbon black in the form of Ni-N4 coordination, and then uses acid etching to remove undesirable Ni nanoparticles formed by the agglomeration of Ni single atoms during the high-temperature carbonization process, and finally obtains Ni single-atom catalysts modified with oxygen-containing functional groups.
[0011] The preparation method provided by the present invention mainly includes two core steps: "introducing oxygen-containing functional groups" and "introducing Ni single atoms by high-temperature carbonization". Among them, high-temperature carbonization treatment is a key step to ensure that Ni single atoms are anchored in the carbon grid of carbon black in the form of Ni-N4 coordination. However, the high-temperature process also destroys some Ni-N4 bonds, causing Ni single atoms to aggregate and form a small amount of Ni nanoparticles. Previous studies have confirmed that O2 molecules tend to be adsorbed on metal nanoparticles in a side group form, which enhances the binding of *OOH on the surface of the material and reduces the selectivity of H2O2. In order to avoid the adverse effect of the presence of Ni nanoparticles on the selectivity of H2O2, the present invention, based on high-temperature carbonization treatment, removes the undesirable Ni nanoparticles formed by the agglomeration of Ni single atoms during the high-temperature carbonization process by acid etching. In the final catalyst, the carbon black surface is loaded with Ni metal active sites dispersed in atomic form, and there are a large number of oxygen-containing functional groups around the Ni single atoms. The synergistic effect of the two is used to improve the adsorption and activation of oxygen molecules on the surface of the material, so that the catalyst has excellent two-electron oxygen reduction performance and excellent selectivity for H2O2. It is applied to a flow electrolytic cell to significantly improve the yield of H2O2.
[0012] Furthermore, step S1 includes: dispersing carbon black in concentrated nitric acid with a concentration of 12-14 mol / L, heating under stirring conditions, and introducing oxygen-containing functional groups on the surface of the carbon black; the product is washed, dried and ground to obtain oxidized carbon black.
[0013] Furthermore, in step S1, the ratio of carbon black to concentrated nitric acid is (1-1.2): 200 g / mL, and the heating treatment is performed in a water bath at a temperature of 80-90° C. for 24-48 hours. The present invention significantly increases the amount of oxygen-containing functional groups around Ni single atoms by increasing the oxidation temperature of carbon black and extending the oxidation time of carbon black.
[0014] Furthermore, in step S2, the nickel salt includes nickel acetate and / or nickel nitrate; the nitrogen-containing organic ligand includes a combination of one or more of 1,10-phenanthroline, melamine, L-alanine, urea, and dicyandiamide; and the solvent is selected from one of ethanol and water.
[0015] Preferably, in step S2, the nickel salt is nickel acetate tetrahydrate, the nitrogen-containing organic ligand is 1,10-phenanthroline monohydrate, and the solvent is ethanol. Nickel acetate tetrahydrate and 1,10-phenanthroline monohydrate are dissolved in ethanol, and Ni and N are coordinated by magnetic stirring to form a Ni-N4 coordination structure. This structure is more stable during high-temperature carbonization, and Ni tends to exist in a single atomic form on the carbon black surface.
[0016] Preferably, in step S2, the mass ratio of nickel acetate tetrahydrate, 1,10-phenanthroline monohydrate and carbon black is (12-13):(29-30):(65-75). In the present invention, by controlling the feed ratio of nickel salt and nitrogen-containing organic ligand to carbon black, the loading amount of nickel single atoms on the surface of the material is controlled to avoid excessive nickel loading and aggregation on the surface of the material to form nanoparticles.
[0017] Furthermore, in step S2, the heating treatment is performed by water bath heating at a temperature of 55-65° C. for 3.5-4.5 h.
[0018] Furthermore, in step S3, the temperature of the high temperature carbonization treatment is 500-800°C and the time is 2-3 h.
[0019] Preferably, the temperature of the high-temperature carbonization treatment is 650-750 °C and the time is 2-3 h. Under such conditions, the catalyst prepared has higher electrocatalytic ORR activity and hydrogen peroxide selectivity.
[0020] Furthermore, the protective atmosphere gas is selected from argon or nitrogen, and the gas flow rate is 60-80 mL / min. The present invention limits the flow rate of the inert gas during the high-temperature carbonization process, making the material easier to carbonize, which helps to anchor the single-atom nickel to the surface of the material.
[0021] Furthermore, in step S4, the third product is dispersed in an acid etchant for acid etching, and the acid etchant is hydrochloric acid or nitric acid. Preferably, the acid etchant is nitric acid, and the third product is subjected to acid etching using nitric acid, which can additionally introduce a portion of oxygen-containing functional groups, further increasing the amount of oxygen-containing functional groups of the catalyst.
[0022] Furthermore, it has been found that when the concentration of the acid etchant is too high, the temperature of the acid etching treatment is too high or the time is too long, the amount of nickel loaded on the carbon black surface will be significantly reduced; and when the temperature of the acid etching treatment is too low or the time is too short, the nanoparticles on the surface of the third product material cannot be effectively removed. Preferably, the concentration of the acid etchant is 1-1.5 mol / L, the temperature of the acid etching treatment is 70-90 °C, and the time is 6-10 h.
[0023] The technical solution adopted by the present invention to achieve the second purpose is to provide a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, which is prepared by the preparation method according to one of the purposes of the present invention.
[0024] The catalyst prepared by the present invention has Ni metal active sites dispersed in atomic form on the surface of carbon black, and a large number of oxygen-containing functional groups exist around the Ni single atom. The synergistic effect of the two improves the adsorption and activation of oxygen molecules on the surface of the material, so that the catalyst has excellent two-electron oxygen reduction performance. According to ICP-MS measurement, the Ni loading of the catalyst is 1.38 wt%; according to XPS measurement and analysis, the O content of the catalyst is 9.05 at%. The synergistic effect of the Ni single atom and the oxygen-containing functional group enables it to have excellent selectivity for reducing O2 to generate H2O2.
[0025] The technical solution adopted by the present invention to achieve the third purpose is to provide an application of the nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide according to one of the purposes of the present invention in the reaction of reducing O2 to generate H2O2.
[0026] The present invention introduces oxygen-containing functional groups near the active center of the Ni single atom to effectively improve the electronic structure of the single atom active site, thereby affecting the adsorption of O2 by the single atom. The prepared catalyst exhibits excellent 2e - ORR selectivity, 0.2 - 0.7 V ( vs. The high selectivity for H2O2 (>92%) is maintained within a large voltage window of RHE. In a flow electrolysis cell test with 0.1 M KOH as the medium, the Faradaic efficiency of H2O2 is close to 100%. -2 Under the condition of , it can run stably for 24 h, and the H2O2 yield is 6.73 mol·g cat -1 ·h -1 , showing broad application prospects.
[0027] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide. First, oxygen-containing functional groups are introduced on the surface of carbon black. Then, using this as a substrate, Ni-N4 complexes are first adsorbed on the surface of carbon black. Then, high-temperature carbonization treatment is used to anchor Ni single atoms in the carbon grid of carbon black in the form of Ni-N4 coordination. Then, acid etching is used to remove undesirable Ni nanoparticles formed by agglomeration of Ni single atoms during the high-temperature carbonization process, and finally, Ni single-atom catalysts modified with oxygen-containing functional groups are obtained. The preparation method has low raw material cost, is easy to control and scale, and has good prospects for industrial application.
[0028] (2) The nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide prepared by the present invention has a large number of Ni metal active sites dispersed in atomic form, and a large number of oxygen-containing functional groups exist around the Ni single atom. The synergistic effect of the two improves the adsorption and activation of oxygen molecules on the surface of the material, so that the catalyst has excellent two-electron oxygen reduction performance at 0.2-0.7 V ( vs. The high selectivity for H2O2 (>92%) is maintained within a large voltage window of RHE. In a flow electrolysis cell test with 0.1 M KOH as the medium, the Faradaic efficiency of H2O2 is close to 100%. -2 Under the condition of , it can run stably for 24 h, and the H2O2 yield is 6.73 mol·g cat -1 ·h -1 , showing broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 a is the scanning electron microscope image of carbon black, Figure 1 b is a scanning electron microscope image of carbon black after oxidation treatment (also a scanning electron microscope image of the product of Comparative Example 1), Figure 1 c is the scanning electron microscope image of Example 1, Figure 1 d is the SEM image of Comparative Example 2, Figure 1 e is the SEM image of Comparative Example 3; Figure 2 a is the transmission electron microscope image of carbon black. Figure 2 b is a transmission electron microscopy image of carbon black after oxidation treatment (also a transmission electron microscopy image of the product of Comparative Example 1), Figure 2 c is the transmission electron microscope image of Example 1, Figure 2 d is the transmission electron microscope image of comparative example 2, Figure 2 e is a high-resolution transmission electron microscopy image of comparative example 2, Figure 2 f is the transmission electron microscope image of comparative example 3; Figure 3 a and Figure 3 b are high-angle annular dark field images of Example 1 and Comparative Example 3 respectively; Figure 4 The XRD patterns of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in FIG. Figure 5 FTIR spectra of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3; Figure 6 a, 6b, 6c, 6d are the ring current density LSV curve, hydrogen peroxide selectivity, disk current density LSV curve and electron transfer number of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively; Figure 7The H2O2 yield and Faraday efficiency at different current densities of Example 1; Figure 8 a is Example 1 at 200 mA cm -2 The stability test current, Figure 8 b is the corresponding cumulative production of hydrogen peroxide and the corresponding Faradaic efficiency. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0032] The present invention provides a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, comprising the following steps: Step 1: Disperse commercial carbon black in a 12-14 mol / L concentrated nitric acid at a ratio of (1-1.2): 200 g / mL, heat and stir in a water bath at 80-90°C for 24-48 hours, introduce oxygen-containing functional groups on the surface of the carbon black, wash the obtained black slurry with pure water and ethanol until it is neutral, then dry it in a vacuum drying oven, and grind the dried material into powder to obtain oxidized carbon black; Step 2: nickel acetate tetrahydrate and 1,10-phenanthroline monohydrate are dissolved in a solvent, and magnetic stirring is performed at room temperature to allow Ni to completely coordinate with N to obtain a first product containing a Ni-N4 complex; then the oxidized carbon black obtained in step 1 is added to the first product, wherein the mass ratio of nickel acetate tetrahydrate, 1,10-phenanthroline monohydrate and carbon black is (12-13):(29-30):(65-75), and the mixture is heated in a water bath at 55-65°C for 3.5-4.5 h to allow the Ni-N4 complex to adsorb on the surface of the carbon black, and the mixture is heated to 75-85°C and continued to be heated to remove the solvent, and then ground to obtain a second product in powder form; Step 3: The second product obtained by grinding in step 2 is transferred to a corundum crucible, and then placed in a tubular furnace. Under a protective atmosphere, the second product is subjected to a high-temperature carbonization treatment. The gas of the protective atmosphere is selected from argon or nitrogen, and the gas flow rate is 60-80 mL / min. The high-temperature carbonization treatment temperature is controlled to be 650-750°C, and the time is 2-3h to obtain a third product in which Ni single atoms and Ni nanoparticles coexist; Step 4: Disperse the third product in an acid etchant for acid etching to remove Ni nanoparticles in the third product. The acid etching uses nitric acid with a concentration of 1-1.5 mol / L, the temperature of the acid etching is 70-90°C, and the time is 6-10h. Then wash with pure water and ethanol until neutral, and then put it into a vacuum drying oven for drying. Grind the dried material into powder to obtain the final product.
[0033] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0034] Example 1 This embodiment provides a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, comprising the following steps: Step 1: Disperse 1.0 g of commercial carbon black in 200 mL of 12 M concentrated nitric acid, heat in a water bath at 80 °C with stirring for 48 h, wash the resulting black slurry with pure water and ethanol until it becomes neutral, then place it in a vacuum drying oven at 80 °C and dry it in vacuum for 12 h. Grind the dried material into powder to obtain oxidized carbon black.
[0035] Step 2: Dissolve 12.4 mg of nickel acetate tetrahydrate and 29.7 mg of 1,10-phenanthroline monohydrate in 2 mL of anhydrous ethanol and stir magnetically at room temperature for about 20 min to allow Ni to fully coordinate with N. Then, add 70.0 mg of the oxidized carbon black prepared in step 1 to the above solution, heat it in a water bath at 60 °C for 4 h, then raise the temperature to 80 °C, and allow the above solution to be completely evaporated and ground under stirring.
[0036] Step 3: The powder obtained by grinding in step 2 was transferred to a corundum crucible, and then placed in a tubular furnace. In an argon gas atmosphere with a flow rate of 70 mL / min, it was subjected to high-temperature pyrolysis and carbonization treatment at 700 °C for 2 h at a heating rate of 10 °C / min to obtain a catalyst in which Ni single atoms and nanoparticles coexisted.
[0037] Step 4: The product obtained in step 3 was dispersed in 1 M HNO3, acid-etched at 80 °C for 6 h, then washed with pure water and ethanol until neutral, and then placed in a vacuum drying oven at 80 °C for 12 h. The dried material was ground into powder to obtain the final product.
[0038] Figure 1 a is the scanning electron microscope image of carbon black, Figure 1 b is the scanning electron microscope image of carbon black after oxidation treatment. Figure 1 c is the SEM image of the product of Example 1. All three show irregular spherical morphology, indicating that acid oxidation and high-temperature carbonization treatment will not change the basic morphology of carbon black. Figure 1c shows that high temperature will cause adhesion between material particles, resulting in material agglomeration.
[0039] Figure 2 a is the transmission electron microscope image of carbon black. Figure 2 b is the transmission electron microscope image of carbon black after oxidation treatment. Figure 2 c is a transmission electron microscope image of the product of Example 1. It also proves that acid oxidation and high temperature carbonization treatment will not change the basic morphology of carbon black. Figure 2 No nanoparticles were found in c, and no bright spots appeared on the diffraction rings in the embedded SAED pattern, indicating that Ni was loaded on the substrate surface in the form of single atoms.
[0040] Figure 3 a is a high-angle annular dark field image of the embodiment, in which the bright spot represents the Ni element, which clearly and intuitively shows that Ni is loaded on the substrate surface in the form of a single atom.
[0041] Figure 4 The XRD patterns of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown. The example has only the diffraction peak of carbon, but no diffraction peak of metal Ni.
[0042] Figure 5 FTIR spectra of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3. It can be seen that the peak of the oxygen-containing functional group in the embodiment is mainly located at 1092 cm -1 The COC peak at 1720 cm -1 The C=O peak at 400 nm almost completely disappears, which is due to the instability and desorption of C=O during the medium and high temperature pyrolysis process.
[0043] Example 2 This embodiment provides a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, comprising the following steps: Step 1: Disperse 1.1 g of commercial carbon black in 200 mL of 13 M concentrated nitric acid, heat in a water bath at 90 °C with stirring for 36 h, wash the resulting black slurry with pure water and ethanol until it becomes neutral, then place it in a vacuum drying oven at 80 °C and dry it in vacuum for 12 h. Grind the dried material into powder to obtain oxidized carbon black.
[0044] Step 2: Dissolve 12 mg of nickel acetate tetrahydrate and 29 mg of 1,10-phenanthroline monohydrate in 2.2 mL of anhydrous ethanol and stir magnetically at room temperature for 25 min to allow Ni to fully coordinate with N. Then add 65 mg of oxidized carbon black prepared in step 1 to the above solution, heat in a water bath at 55 °C for 3.5 h, then raise the temperature to 80 °C, allow the above solution to be completely evaporated and ground under stirring.
[0045] Step 3: The powder obtained by grinding in step 2 was transferred to a corundum crucible, and then placed in a tubular furnace. In an argon gas atmosphere with a flow rate of 80 mL / min, it was subjected to high-temperature pyrolysis and carbonization treatment at 750 °C for 2.5 h with a heating rate of 12 °C / min to obtain a catalyst in which Ni single atoms and nanoparticles coexisted.
[0046] Step 4: The product obtained in step 3 was dispersed in 1.2 M HNO3, acid-etched at 70 °C for 8 h, then washed with pure water and ethanol until neutral, and then placed in a vacuum drying oven at 80 °C for 12 h. The dried material was ground into powder to obtain the final product.
[0047] Example 3 This embodiment provides a method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, comprising the following steps: Step 1: Disperse 1.2 g of commercial carbon black in 200 mL of 14 M concentrated nitric acid, heat in a water bath at 85 °C with stirring for 24 h, wash the resulting black slurry with pure water and ethanol until it becomes neutral, then place it in a vacuum drying oven at 80 °C and dry it in vacuum for 12 h. Grind the dried material into powder to obtain oxidized carbon black.
[0048] Step 2: Dissolve 13 mg of nickel acetate tetrahydrate and 30 mg of 1,10-phenanthroline monohydrate in 2.5 mL of anhydrous ethanol and stir magnetically at room temperature for 20 min to allow complete coordination between Ni and N. Then add 75 mg of oxidized carbon black prepared in step 1 to the above solution, heat in a water bath at 65 °C for 4.5 h, then raise the temperature to 80 °C, allow the above solution to be completely evaporated and ground under stirring.
[0049] Step 3: The powder obtained by grinding in step 2 was transferred to a corundum crucible, and then placed in a tubular furnace. In an argon gas atmosphere with a flow rate of 70 mL / min, it was subjected to high-temperature pyrolysis and carbonization treatment at 650 °C for 3 h at a heating rate of 8 °C / min to obtain a catalyst in which Ni single atoms and nanoparticles coexisted.
[0050] Step 4: The product obtained in step 3 was dispersed in 1.5 M HNO3, acid-etched at 90 °C for 10 h, then washed with pure water and ethanol until neutral, and then placed in a vacuum drying oven at 80 °C for 12 h. The dried material was ground into powder to obtain the final product.
[0051] Comparative Example 1 This comparative example is the same as step 1 of Example 1, and oxidized carbon black is prepared by the following specific operations: 1.0 g of commercial carbon black was dispersed in 200 mL of 12 M concentrated nitric acid, heated in a water bath at 80 °C with stirring for 48 h, the obtained black slurry was washed with pure water and ethanol until neutral, and then placed in a vacuum drying oven at 80 °C for 12 h. The dried material was ground into powder to obtain oxidized carbon black.
[0052] Figure 5 FTIR spectra of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3. It can be seen that the oxygen-containing functional groups introduced on the surface of carbon black by nitric acid oxidation are mainly COC (1092 cm -1 ) and C=O (1720 cm -1 ).
[0053] Comparative Example 2 This comparative example is the same as steps 1-3 of Example 1, except that the acid etching treatment in step 4 is not included in this comparative example. The specific operation is as follows: Step 1: Disperse 1.0 g of commercial carbon black in 200 mL of 12 M concentrated nitric acid, heat in a water bath at 80 °C with stirring for 48 h, wash the resulting black slurry with pure water and ethanol until it becomes neutral, then place it in a vacuum drying oven at 80 °C and dry it in vacuum for 12 h. Grind the dried material into powder to obtain oxidized carbon black.
[0054] Step 2: Dissolve 12.4 mg of nickel acetate tetrahydrate and 29.7 mg of 1,10-phenanthroline monohydrate in 2 mL of anhydrous ethanol and stir magnetically at room temperature for about 20 min to allow Ni to fully coordinate with N. Then, add 70.0 mg of the oxidized carbon black prepared in step 1 to the above solution, heat it in a water bath at 60 °C for 4 h, then raise the temperature to 80 °C, and allow the above solution to be completely evaporated and ground under stirring.
[0055] Step 3: The powder obtained by grinding in step 2 is transferred to a corundum crucible, and then placed in a tubular furnace. In an argon atmosphere, it is subjected to high-temperature pyrolysis and carbonization treatment at 700 °C for 2 h at a heating rate of 10 °C / min to obtain a catalyst in which Ni single atoms and nanoparticles coexist.
[0056] Figure 1 d is a scanning electron microscope image of comparative example 2. It can be seen that, similar to the embodiment, the particles in comparative example 2 are also approximately spherical in shape and also agglomerate under the action of high temperature.
[0057] Figure 2 d is the transmission electron microscopy image of comparative example 2. It can be seen that a large number of Ni nanoparticles appear in comparative example 2. Figure 2 e is a high-resolution transmission electron microscopy image of comparative example 2, in which the lattice spacing is 0.21 nm, corresponding to the (111) crystal plane of Ni.
[0058] Figure 4 In the comparative example 2, a strong diffraction peak of metal Ni appears, indicating that there are a large number of Ni nanoparticles in the comparative example 2. Figure 2 d is consistent with the transmission result.
[0059] Figure 5 In Example 1, the peak of the oxygen-containing functional group in Comparative Example 2 is also mainly located at 1092 cm -1 There is almost no COC peak at 1720 cm -1 The C=O peak at .
[0060] Comparative Example 3 The difference between this comparative example and Example 1 is that the step of oxidizing carbon black in step 1 is not included in this comparative example, and commercial carbon black is directly used as the substrate. In addition, in order to avoid the introduction of oxygen-containing functional groups during the acid etching process, HNO3 in step 4 is replaced with HCl of the same concentration, and the specific operation is as follows: Step 1: Dissolve 12.4 mg of nickel acetate tetrahydrate and 29.7 mg of 1,10-phenanthroline monohydrate in 2 mL of anhydrous ethanol and stir magnetically at room temperature for about 20 min to allow complete coordination between Ni and N. Then add 70.0 mg of pristine carbon black to the solution, heat it in a water bath at 60 °C for 4 h, then raise the temperature to 80 °C, allow the solution to completely evaporate to dryness under stirring, and grind.
[0061] Step 2: The powder obtained by grinding in step 1 is transferred to a corundum crucible, and then placed in a tube furnace. In an argon atmosphere, it is subjected to high-temperature pyrolysis and carbonization treatment at 700 °C for 2 h at a heating rate of 10 °C / min to obtain a catalyst in which Ni single atoms and nanoparticles coexist.
[0062] Step 3: The product obtained in step 2 was dispersed in 1 M HCl, acid-etched at 80 °C for 6 h, then washed with pure water and ethanol until neutral, and then placed in a vacuum drying oven at 80 °C for 12 h. The dried material was ground into powder to obtain the final product.
[0063] Figure 1 e is a scanning electron microscope image of comparative example 3. It can be seen that similar to Example 1, the particles in comparative example 3 are also approximately spherical in shape and also agglomerate under high temperature.
[0064] Figure 2 e is a transmission electron microscope image of comparative example 3. No nanoparticles were found in comparative example 3, and no bright spots appeared on the diffraction rings in the embedded SAED image, indicating that Ni was loaded on the substrate surface in the form of single atoms.
[0065] Figure 3b is the high-angle annular dark field image of Example 3, which can also clearly and intuitively show that Ni is loaded on the substrate surface in the form of single atoms.
[0066] Figure 4 In the example, the XRD spectrum of comparative example 3 also has only the diffraction peak of carbon, and no diffraction peak of metal Ni is observed.
[0067] Figure 5 In the example, the peak of the oxygen-containing functional group in Comparative Example 3 is also mainly located at 1092 cm -1 There is almost no COC peak at 1720 cm -1 The C=O peak at .
[0068] Application performance testing (I) Testing the 2 e of the catalysts prepared in the above examples - ORR H2O2 production performance: Rotating ring disk electrode (RRDE) measurements were performed using a typical three-electrode system in 0.1 M KOH (pH = 12.99) at room temperature (25 °C) using an electrochemical workstation (CHI 760E, CH Instruments). A carbon rod and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively, and a rotating ring disk electrode (RRDE, American Pine Instruments, disk area: 0.196 cm) was used as the working electrode. 2 , Ring area: 0.1866 cm 2 The catalyst ink was prepared as follows: First, 2 mg of the prepared catalyst and 20 uL of Nafion solution (5 wt.%) were added to 0.98 mL of a mixed solution of water and anhydrous ethanol (V 水 :V 乙醇 = 10:88); then, the above solution was ultrasonically treated for 30 min to form a uniformly dispersed ink; finally, 9.8 uL of the ink was evenly coated on a glassy carbon disk and fully air-dried, with a loading of 0.1 mg cm -2 Before measuring ORR, the electrolyte was saturated with N2 at 20 mV s -1 The scan rate was between 0 and 1.0 V ( vs At least 50 cyclic voltammetric scans were performed at 1600 rpm between RHE and O2 to obtain a stable cyclic voltammetric curve. Then, the cyclic voltammetric curve was scanned at 10 mV s -1 The scan rate was between 0 and 1.0 V ( vsPolarization curves and rotating ring disk electrode (RRDE) measurements were performed at 1600 rpm between RHE and the Pt ring electrode while the potential of the Pt ring electrode was kept at 1.2 V ( vs . RHE), and thus the oxygen reduction activity and selectivity were studied. The H2O2 selectivity and the number of electron transfers can be obtained by obtaining the disk current I d and the ring current I r , calculated according to the following formula:
[0069] Among them, I d is the disk current, I r is the ring current, and N is the collection efficiency of the Pt ring, which is 41%.
[0070] Depend on Figure 6 It can be seen that the embodiment has a larger disk current and ring current than the comparative example 1. In the window of 0.2-0.7V (vs. RHE), the hydrogen peroxide selectivity of the embodiment is greater than 92%, and the electron transfer number is close to 2, which is better than the comparative example 1. This shows that the introduction of Ni single atoms can improve the activity of the oxygen reduction reaction and the selectivity of generating hydrogen peroxide. The disk current of comparative example 2 is greater than that of the embodiment, but its ring current is much smaller, so that the hydrogen peroxide selectivity of comparative example 2 is much smaller than that of the embodiment, only 40-60%. The disk current of comparative example 3 is slightly smaller than that of the embodiment, but the ring current is only half of that of the embodiment, and the selectivity of hydrogen peroxide is 60-70%. It can be seen that the presence of oxygen-containing functional groups is conducive to improving the selectivity of hydrogen peroxide. At the same time, the introduction of Ni single atoms and oxygen-containing functional groups, the synergistic effect of the two is exerted, which not only improves the oxygen reduction activity, but also improves the selectivity of two-electron oxygen reduction.
[0071] (II) Actual production of H2O2 under different currents in Test Example 1: The electrocatalytic H2O2 production rate, Faraday efficiency FE and stability of the catalyst were tested using a three-electrode flow electrolysis cell. 3.2 mg of the catalyst was dispersed in a mixed solution of 0.88 mL of ethanol, 0.1 mL of water and 0.02 mL of Nafion (5 wt%) and ultrasonicated for 30 min to prepare the catalyst ink. The prepared ink was drop-coated on a 6.4 cm 2 The hydrophobic carbon paper (actual working area is 4.0 cm 2 The catalyst loading was 0.5 mg / cm 2) and dried with an infrared lamp. The catalyst-modified carbon paper was then used as the working electrode of the flow electrolytic cell, the Ag / AgCl electrode was used as the reference electrode, and the commercial Pt sheet was used as the counter electrode. A gas diffusion channel was provided on the cathode side of the electrolytic cell. During the reaction, O2 was continuously introduced into the diffusion channel at a flow rate of 10 mL / min. The anode and cathode chambers were separated by a proton exchange membrane (Nafion 117). After the test started, 50 μL was taken out from the cathode liquid every 15 min to determine the concentration of H2O2 produced. The H2O2 concentration was determined by the traditional cerium sulfate titration method. Specifically, the yellow Ce 4+ Can be reduced by H2O2 to form colorless Ce 3+ (See formula 3), Ce before and after the reaction 4+ The concentration can be measured by a UV-visible spectrophotometer with a test wavelength of 317 nm, which can indirectly obtain the H2O2 concentration (see formula 4).
[0072]
[0073] Yes Ce 4+ The initial concentration is 1 mM. After mixing with H2O2 4+ The mixed solution was diluted to 10 mL. is the volume of H2O2 in mL.
[0074] Prepare 1 mM Ce(SO4)2 by dissolving 332 mg Ce(SO4)2 in 1 L 0.5 M H2SO4.
[0075] The Faraday efficiency FE can be calculated by the following formula 5:
[0076] Figure 7 The H2O2 yield and Faraday efficiency of the embodiment at different current densities. In the 2 h test at different current densities, the H2O2 yield basically showed a linear growth. -2 The embodiment still has a high Faradaic efficiency (91.4%) under high current, and the H2O2 yield can reach 6.91 mol g cat -1 h -1 .
[0077] Figure 8 a is the experimental example at 200 mA cm -2 The stability test current, Figure 8 b is the corresponding cumulative production of hydrogen peroxide and the corresponding Faraday efficiency. Example at 200 mA cm-2 The system can still run stably for 24 h under high current. During the whole test period, FE is kept above 90% and H2O2 yield is kept stable at 6.73 mol g cat -1 h -1 The electrochemical stability of the embodiment is proved, and it has broad application prospects.
[0078] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, characterized in that: The following steps are involved: S1. Introducing oxygen-containing functional groups on the surface of carbon black to obtain oxidized carbon black; S2, dissolving the nickel salt and the nitrogen-containing organic ligand in a solvent, and mixing them thoroughly to obtain a first product containing a Ni-N4 complex; adding the oxidized carbon black to the first product, heating the product so that the Ni-N4 complex is adsorbed on the surface of the carbon black, continuing to heat the product to remove the solvent, and then grinding the product to obtain a powdery second product; S3, subjecting the second product to high-temperature carbonization treatment under a protective atmosphere to obtain a third product in which Ni single atoms and Ni nanoparticles coexist; S4. Removing the Ni nanoparticles in the third product by acid etching to obtain the final product.
2. The preparation method according to claim 1, characterized in that: Step S1 includes: dispersing carbon black in concentrated nitric acid with a concentration of 12-14 mol / L, heating under stirring conditions, and introducing oxygen-containing functional groups on the surface of the carbon black; washing, drying and grinding the product to obtain oxidized carbon black.
3. The preparation method according to claim 2, characterized in that: In step S1, the usage ratio of carbon black to concentrated nitric acid is (1-1.2):200 g / mL, and the heating treatment is carried out by water bath heating at a temperature of 80-90° C. for 24-48 h.
4. The preparation method according to claim 1, characterized in that: In step S2, the nickel salt includes nickel acetate and / or nickel nitrate; the nitrogen-containing organic ligand includes a combination of one or more of 1,10-phenanthroline, melamine, L-alanine, urea, and dicyandiamide; and the solvent is selected from one of ethanol and water.
5. The preparation method according to claim 1, characterized in that: In step S2, the nickel salt is nickel acetate tetrahydrate, and the nitrogen-containing organic ligand is 1,10-phenanthroline monohydrate; the mass ratio of nickel acetate tetrahydrate, 1,10-phenanthroline monohydrate, and carbon black is (12-13):(29-30):(65-75).
6. The preparation method according to claim 1, characterized in that In step S2, the heating treatment is performed in a water bath at a temperature of 55-65° C. for 3.5-4.5 h.
7. The preparation method according to claim 1, characterized in that In step S3, the high temperature carbonization treatment is carried out at a temperature of 500-800°C and a time of 2-3 h.
8. The preparation method according to claim 1, characterized in that In step S4, the third product is dispersed in an acid etchant for acid etching. The acid etchant is hydrochloric acid or nitric acid with a concentration of 1-1.5 mol / L. The temperature of the acid etching is 70-90° C. and the time is 6-10 h.
9. A nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nickel-oxygen modified carbon black catalyst for electrocatalytic synthesis of hydrogen peroxide according to claim 9 in the reaction of reducing O2 to generate H2O2.